The Effect of Giving Combination Concentration of Leaves of Moringa oleifera with Walne Fertilizer in Culture Media on the Growth and Content of Carotenoids in Dunaliella salina - Nurita Wahyuni; Boedi Setya Rahardja; Muhammad Hanif Azhar (Journal of Aquaculture Science, 2019)
The purpose of this study was to determine the effect and optimal dose of addition of Moringa oleifera leaf extract on culture media to the growth and content of carotenoids of Dunaliella salina. The research method used was experimental with Completely Randomized Design (CRD) as the experimental design. The treatments used were different doses of Moringa leaf extract, namely A (100% walne media), B (75% Media walne + 25% Moringa leaf extract), C (50% Media walne + 50% Moringa leaf extract), D ( 25% Media walne + 75% Moringa leaf extract), E (100% Moringa leaf extract) with a dose of Moringa leaf extract that is 28 ml (100%) with repetitions 4 times. The results showed that the addition of Moringa oleifera leaf extract had a significantly different effect (P <0.05) on growth. Based on the density of Dunaliella salina showed the best treatment, namely at treatment B (75% walne + 25% Moringa extract). The best specific growth rate is found in treatment B (75% walne + 25% Moringa extract). The carotenoid content after treatment was not significantly different (P> 0.05) so that the carotenoid content in the control (treatment A) had the highest level of 1.39 µg / ml and the lowest was in treatment C of 0.19 µg / ml.